Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/jacs.9b07785
|View full text |Cite
|
Sign up to set email alerts
|

Active Patchy Colloids with Shape-Tunable Dynamics

Abstract: Controlling the complex dynamics of active colloidsthe autonomous locomotion of colloidal particles and their spontaneous assemblyis challenging yet crucial for creating functional, out-of-equilibrium colloidal systems potentially useful for nano- and micromachines. Herein, by introducing the synthesis of active “patchy” colloids of various low-symmetry shapes, we demonstrate that the dynamics of such systems can be precisely tuned. The low-symmetry patchy colloids are made in bulk via a cluster-encapsulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 66 publications
(109 reference statements)
0
79
0
Order By: Relevance
“…Colloidal molecules (CMs) are well-dened colloidal clusters with precise symmetry of molecular structures and have drawn extensive interest because of their unique properties 1,2 and potential as building blocks for low-coordination open structures. 3,4 With compartmental functional domains and directional interaction, CMs are promising in biological and medical applications, 5,6 self-assembly, 7,8 physical chemistry, [9][10][11] and materials science and technology. [12][13][14] Through particle-based self-assembly, CMs with molecule-like symmetries are enabled using monodisperse patchy building blocks with a suitable shape or interaction anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…Colloidal molecules (CMs) are well-dened colloidal clusters with precise symmetry of molecular structures and have drawn extensive interest because of their unique properties 1,2 and potential as building blocks for low-coordination open structures. 3,4 With compartmental functional domains and directional interaction, CMs are promising in biological and medical applications, 5,6 self-assembly, 7,8 physical chemistry, [9][10][11] and materials science and technology. [12][13][14] Through particle-based self-assembly, CMs with molecule-like symmetries are enabled using monodisperse patchy building blocks with a suitable shape or interaction anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…Having shown the size-selective bonding based on simple spheres, we seek to build (selective and) directional bonds by utilizing anisotropic particles as ligands, in our case metallodielectric patchy particles each having a metallic (gold) lobe and a dielectric (polymer) lobe. The patchy particles are synthesized via a surfactant-aided dewetting method we recently developed 59 . The size of the two lobes and the particle's aspect ratio can be independently addressed (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In these examples, we note that the combination of selective directional bonds and particle activity is even more critical and requires complex particles to carry all the necessary information. The use of particles with multiple patches and tunable shapes and compositions may provide a solution 59 . In all cases, fine control of the interparticle interactions, including both the static and dynamic ones, is key.…”
Section: Discussionmentioning
confidence: 99%
“…One such study showed that L-shaped particles exhibit circular trajectories. 22 More recent experiments on select anisotropic shapes or patches confirmed some of the predictions in 2D [23][24][25][26] and found unexpected motion patterns such as non-cylindrical helices 27 in 3D. Still, the current limitations in particle design prevent a systematic comparison with theory.…”
Section: Introductionmentioning
confidence: 91%